The Business Student's Guide to Study and Employability - Peter Morgan (Norderstedt, Germany Sage, 2021)
Written in response to the pressures on universities to produce highly skilled and work-ready graduates and intended to map across a three-year business course, this book covers essential skills, from study, presentation and leadership to practical advice on securing that all-important job after university. A number of hands-on learning aids feature throughout, including: Skills self-assessment tables, 'For You to Do', Integration and Application, Interview questions. This second edition has been thoroughly updated, and is complemented by a companion website featuring a range of tools and resources for lecturers and students, including an Instructor's Manual and PowerPoint slides, answers and guidance on skills assessment tasks, templates and examples to download as well as additional online chapters on topics such as testing, assessment and alternative options for graduates. Suitable for all students taking a business degree.
Keywords: Business; (MGT102) Business Management Skills Development